Impacts of translated afro-futurism themes in early childhood education for cultural competence in Anambra state Nigeria - Josephine Obiageli Okafor (Piramida Akademi, 2025)
This study aimed to assess the impact of implementing translated Afro-futurism themes in early childhood education on cultural competence among primary school teachers in Anambra State, Nigeria. Adopting a survey design, the research utilized self-structured questionnaires distributed via Google Survey to accommodate the schedules of participants, ensuring they could respond at their convenience. To validate the survey instrument, feedback was sought from three experts in Measurement and Evaluation, affirming the questionnaire's validity. Reliability was confirmed through Cronbach's alpha coefficient, achieving a satisfactory reliability score of 0.84. The study's primary data source was a sample of 121 primary school teachers who completed the online survey. In examining the gathered information, the researcher applied different factual strategies. Frequency counts and percentages were utilized to sum up segment data. To address the examination questions, mean scores and standard deviations were determined, giving experiences into the members' points of view. Also, Analysis of Variance (ANOVA) was utilized to test the hypotheses, deciding the measurable meaning of any distinctions noticed. The analysis reveals significant differences in both teachers' perception of translated Afro-futurism themes across gender and the impacts of such content on children's cultural understanding based on teachers' years of experience. These findings highlight the importance of considering both gender and experience levels in implementing Afro-futurism in education. This systemic methodology worked with a thorough assessment of how integrating Afro-futurism into early childhood education influences cultural competence, offering significant bits of knowledge for teachers and policymakers in Anambra State and potentially beyond.